The Role of Law in Regulating Corporate Obligations to Environmental and Social Welfare - Irwan Saputra; Irfan Rizky Hutomo; Tri Susilowati (Indonesian Journal Publisher, 2026)
In the era of globalization and rapid industrial development, the role of companies is includes social and environmental responsibilities in addition to financial gain. This responsibility is realized through various policies aimed at maintaining a balance between business interests, community welfare, and environmental sustainability. Therefore, the law plays a very important role in regulating corporate obligations to contribute to sustainable development. Various legal instruments, both nationally and internationally, have been designed to ensure companies comply with applicable environmental and social standards. These regulations include the Environmental Law, the Sustainable Development Goals (SDGs) and the principles of Good Corporate Governance (GCG) through the Limited Liability Company Law and other Corporate Social Responsibility (CSR) legislation. This study strives to analyze the role of law in regulating corporate obligations towards environmental and social welfare by reviewing various laws and relevant international legal instruments. The approach used in this study is the normative juridical method, namely by analyzing applicable legal regulations and legal doctrines related to corporate responsibility. This study was conducted through a literature review of primary legal sources, such as laws and regulations, as well as secondary legal sources in the form of journals, books, and other legal documents. Using this approach, the study aims to give a summary of how well the law regulates corporate obligations and to pinpoint the difficulties encountered when putting these requirements into practice. It is anticipated that the findings of this study will aid in the creation of more efficient legislative regulations for overseeing and upholding corporate social and environmental commitments.